2008 IEEE 35th International Conference on Plasma Science 2008
DOI: 10.1109/plasma.2008.4591000
|View full text |Cite
|
Sign up to set email alerts
|

Radial wire array Z-pinches as a novel, compact x-ray source

Abstract: Wire array z-pinches are the world's most powerful laboratory x-ray source, however the large volume required for them to work efficiently requires the use of a large hohlraum for inertial confinement fusion applications. This hohlraum size limits the temperature achievable using present pulsed power capabilities. Whilst work is continuing to improve the efficiency of cylindrical wire arrays, an alternative is to use an array configuration that is better suited to a smaller hohlraum. Radial wire arrays have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Lebedev 2005;Ampleford et al 2008) have also shown the development of conical shocks forming at the base and along the axis of the developed jet.…”
Section: Jets and Multiple Oblique Shocksmentioning
confidence: 99%
“…Lebedev 2005;Ampleford et al 2008) have also shown the development of conical shocks forming at the base and along the axis of the developed jet.…”
Section: Jets and Multiple Oblique Shocksmentioning
confidence: 99%
“…Lebedev et al 2005;Ampleford et al 2008) have shown development of oblique or conical shocks forming at the base of a supersonic jet and along its axis. The latest observations have witnessed a development of standing or traveling shocks in many astrophysical objects, and most prominently in AGN jets (e.g.…”
mentioning
confidence: 99%